Mobile Multimedia Communications 7th International ICST Conference, MOBIMEDIA 2011, Cagliari, Italy, September 5-7, 2011, Revised Selected Papers - Atzori, Luigi; Delgado, Jaime; Giusto, Daniele; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 7th International ICST Conference on Mobile Multimedia Communications (MOBIMEDIA 2011) held in Cagliari, Italy, in September 2011 The 26 revised full papers presented were carefully selected from numerous submissions and focus topics such as quality of experience, dynamic spectrum access wireless networks in the TV white spaces, media streaming, mobile visual search, image processing and transmission, and mobile applications.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information storage and retrieval systems; Artificial intelligence; Computer vision; Computer Science; Information Systems Applications (incl. Internet).; Computer Communication Networks; Information Storage and Retrieval; Artificial Intelligence (incl. Robotics).; Computer Imaging, Vision, Pattern Recognition and Graphics; Software Engineering